A longitudinal study of the life histories of people with spinal cord injury. Issue 6 (28th September 2010) - Sullivan, Martin; Paul, Charlotte E; Herbison, G Peter; Tamou, Peina; Derrett, Sarah; Crawford, Maureen
Abstract : Background: Approximately 70–80 New Zealanders have spinal cord impairment (SCI) due to injury (2/3) or disease (1/3) each year. They had been socialised as non-disabled people. Following paralysis, interrelationships between body, self and society change. Little is known of the impact of these changes on life histories, life chances and life choices of people with SCI. This has negative implications for the design of rehabilitation and disability support services in New Zealand. Furthermore, the trajectory of disability is affected by previous socioeconomic conditions. How specific supports following SCI (eg, rehabilitation and compensation funded by the Accident Compensation Corporation; ACC) can change this trajectory is unknown. Objectives: To explore the interrelationships of body, self and society for people with SCI and how these have shaped life chances, life choices and subjectivity. To investigate how entitlement to rehabilitation and compensation through ACC affects socioeconomic and health outcomes. Setting: New Zealand. Design: A prospective cohort study; mixed methods. Participants: 112 people with SCI admitted for the first time to one of New Zealand's two spinal units without serious cognitive injury. Data: Structured interviews with all participants (n=112); qualitative interviews with a selected subgroup (n=20); clinical data collected at the time of admission. Exposures include: demographics, comorbidity, previoius health and socioeconomic status, SCI resulting from illness or injury, income support, health and social services. Outcome measures: Socioeconomic status, health, participation and life satisfaction. Analysis: Descriptive statistics; differences tested by paired t tests or McNemar tests; multiple regression and mixed models. Qualitative analysis will be interpretive.